The Need and Desire for Mental Health and Substance Use–Related Services Among Clients of Publicly Funded Sexually Transmitted Infection Clinics in Vancouver, Canada. Issue 3 (May 2019) - Salway, Travis; Ferlatte, Olivier; Shoveller, Jean; Purdie, Aaron; Grennan, Troy; Tan, Darrell H. S.; Consolacion, Theodora; Rich, Ashleigh J.; Dove, Naomi; Samji, Hasina; Scott, Kai; Blackwell, Everett; et al.
Abstract : Context: Sexually transmitted infections (STI) and mental health and substance use (MHSU) disorders all occur at elevated rates in sexual and gender minorities. These overlapping epidemics, or syndemics, are exacerbated by challenges these same populations face in accessing sexual/gender minority-affirming services. Many publicly funded STI clinics are a low barrier and provide sexual minority-competent care. These sites therefore may be uniquely situated to address clients' MHSU-related needs. Objective: We characterize the need and desire for MHSU services among STI clinic clients. Design, Setting, Participants: We conducted a waiting room survey at 6 STI clinics in Metro Vancouver, Canada. Main Outcome Measures: We calculated the proportion of clients with self-reported unmet MHSU needs in the previous 12 months and, among these clients, barriers to accessing MHSU services and desire for MHSU services within the STI clinic. We also examined social disparities in barriers to accessing MHSU services. Results: Among 1115 respondents—65% of whom were sexual minorities—39% reported a recent need for MHSU-related care, most frequently in relation to anxiety (29%), depression (26%), substance use (10%), or suicide ideation (7%). Seventy-two percent of this group had not yet talked to a provider about their concern. Common barriers included shame (26%) and inability to afford the service (24%). Eighty-three percent of clients with unmet MHSU needs indicated that they were comfortable discussing MHSU concerns with an STI clinic provider, and 94% expressed desire to receive MHSU assessments, referrals, or counseling in the STI clinic. Sexual and gender minorities and those attending a suburban clinic were more likely to report barriers to accessing MHSU services. Conclusions: More than a quarter of STI clinic clients report unmet MHSU health care needs; moreover, these clients report high levels of comfort with and desire to discuss MHSU concerns with STI clinic providers. Sexually transmitted infections clinics are thus opportune sites for syndemic service integration.